Teacher Competency Training as a Form of Best Practice for Promoting Teacher's Professional Development - Abbas, Azwar (Mutiara Intelektual Indonesia Press, 2025)
Training is needed to help teachers to improve their competence. This is important because teachers are the core role in the world of education and as a determinant of the future of the nation's children. The state also provides an obligation for teachers to have certain competencies as a condition of the profession. This study aims to find out the training has been held at school as a form of best practice for teacher's professional development, then to reveal how the training affects teachers. This research is descriptive research with a qualitative approach. The research subject is one of the teachers of SD Muhammadiyah Ambarbinangun. Researchers used interviews to collect data. The instrument used was an interview guideline adapted from previous research. The data analysis technique used in this research is qualitative data analysis, namely data reduction, data visualization, and conclusion drawing/verification. There are several trainings that have been sought by the school, namely training aimed at improving pedagogic and personality competencies. This training is quite influential for teachers because several learning objectives are achieved after attending this training, such as increased student grades, more intense communication between teachers and students, more interesting learning in the classroom